Research on the design method of flexural capacity of RC beams strengthen by ultra-high-performance concrete - Jiawei Wang; Feifei Ying (Archives of Civil Engineering, 2024)
Due to the increase in traffic volume, load level, and service life of existing bridges, the bending bearing capacity of reinforced concrete beams (hereinafter referred to as RC beams) has decreased, leading to safety issues. In order to solve the problem of insufficient flexural bearing capacity of RC beams, this article adopts the method of ultra-high performance concrete (UHPC) flexural strengthening RC beams, establishes a finite element model of UHPC-RC reinforcement system, and conducts stress analysis with reinforcement thickness, reinforcement range, reinforcement form, and reinforcement height as parameters to determine the optimal scheme of the reinforcement system. Based on the calculation results, a theoretical formula for the maximum principal stress and maximum deflection of the reinforcement system is proposed. To verify the feasibility of the plan, a reinforcement design was carried out on an existing beam, and it was found that the bending bearing capacity of the RC beam increased by 21%; the high tensile strength of UHPC and the addition of steel fibers have a good limiting effect on cracks; The steel plate of the reinforcement system can be used as a template, reducing construction costs and having good economy.